Impact of Radiometric Calibration and Specifications of Spaceborne Optical Imaging Sensors on the Development of Operational Automatic Remote Sensing Image Understanding Systems - Baraldi, Andrea (IEEE journal of selected topics in applied earth observations and remote sensing, 2009)
The development of operational automatic remote sensing (RS) image understanding systems (RS-IUSs) represents a traditional goal of the RS community. Unfortunately, to date, the transformation of huge amounts of multisource, multiresolution Earth observation (EO) imagery into information still remains far below reasonable expectations. The original contribution of this work to existing knowledge on the subject of automating the quantitative analysis of EO images is fourfold. In primis this paper moves from existing literature to consider the radiometric calibration of RS images a necessary, although not sufficient , condition for implementation of operational automatic RS-IUSs. This requirement complements the traditional perception of calibration and validation (Cal/Val)-related activities as crucial in achieving harmonization and interoperability of multisource EO data and derived information products generated at all scales as envisaged under: (i) the Global Monitoring for the Environment and Security (GMES) project, led by the European Union (EU), and (ii) the Global Earth Observation System of Systems (GEOSS) program, conceived by the Group on Earth Observations (GEO) whose space arm, the Committee of Earth Observations (CEOS), recently delivered a Quality Assurance Framework for Earth Observation (QA4EO) data. The second objective of this paper is to solicit the RS community to further investigate the calibration quality and uncertainty of the well-known Satellite Pour l'Observation de la Terre (SPOT) and Indian Remote sensing Satellite (IRS) imaging sensor series whose zero-value offset parameters appear questionable based on experimental evidence. Third, this work provides a quantitative assessment of the spectral information loss that, in comparison with the ongoing SPOT-4/-5 optical sensors, may affect future planned European EO satellites such as Pleiades-1/-2 and the follow-on missions Astrium SPOT-6/-7. Finally, this work shows that, in several recent or ongoing scientific applications of EO images acquired across time, space, and sensors, the mandatory radiometric calibration preprocessing stage appears to be surprisingly ignored or underestimated by EU space agencies and research institutions that have been members of the CEOS for more than twenty years and should be eager to transform the new QA4EO initiative into RS common practice.